Crônicas da barraria de Alexandre Gomes de Brito: traços do contexto sociocultural. - Wanderley, Josiane da Cruz Tristão (Universidade Federal do Tocantins, 2022)
This paper aims to analyze two chronicles of the work Chronicles of Barraria, by the author Alexandre Gomes Brito (2019), highlighting some socio-cultural aspects presented in the texts written by the author, since in the chronicles in question, we observed a significant amount of social and cultural aspects. being narrated and commented by the author. The chronicles that will be our object of analysis are: Barraria and Marriage in the field. The main authors behind this work are Deboni (2011), Sanches (2008), Le Goff (1990) Bergson (1999). To develop this work we use the bibliographic research, using theoretical books, articles and scientific journals. To facilitate the research, the method of recording the material used was used. In the analysis we discuss about the sociocultural context described by the author, we try to show that the author somehow tries to preserve the culture and uniqueness of that people. From the conception that the text leaves marks of the sociocultural context described by the author, we can infer that there are also marks in the text that are produced by the author. Such marks are observed by us in this work, especially regarding sociocultural traits. In this context, the main purpose of this work is to analyze social and cultural aspects that are narrated and commented by the author during the work.